Cambios estructurales en la participación laboral en Colombia desde 1984 - 2008: un análisis econométrico del mercado laboral urbano para la generación de políticas de empleo (2011)
This study of labor supply, proposes, from a theoretical perspective, identifying the determinants of labor force participation that explain the increased supply of Colombian labor market for different population groups that make up the workforce, It also intends, as an econometric exercise, to determine the influence of a set of variables on the probability of participation of different population groups in the labor market. This study aims to identify structural changes in the determinants of labor participation in Colombia from 1984 to 2008, among different population groups, which contribute to the generation of public employment policies. The estimated probability functions of labor participation will be based on the design of a probit type econometric model of binary choice. According to the results obtained, we can say that the overall participation rate in the seven major metropolitan areas in Colombia is affected positively by the economic growth rate and the head of household, which would lead to increase the supply of work and increase people's participation in the labor market with better job opportunities and wages.